A Comparison Tool For Quality Software Requirement Specification - Novi Trisman Hadi; Ari Firmanto (Engineering Software Requirements, 2018)
Most of the problems in software development come from a bad requirement specification. Failure on the requirements gathering phase is usually caused by unclear, ambiguous, inconsistent or incomplete requirements [1]. Thus, many researchers work on how to improve the quality of requirement specification. Even this is not the largest task of a project, it is really important to provide a flawless requirement specification